Effects of Larval Nutrition on Wolbachia-Based Dengue Virus Interference in Aedes aegypti (Diptera: Culicidae). Issue 4 (22nd April 2016) - Kho, Elise A.; Hugo, Leon E.; Lu, Guangjin; Smith, David D.; Kay, Brian H.
Abstract: In order to assess the broad-scale applicability of field releases of Wolbachia for the biological control of insect-transmitted diseases, we determined the relationship between the larval diet of Aedes aegypti L. mosquitoes infected with Wolbachia strains and their susceptibility to dengue virus (DENV) infection via intrathoracic injection and oral inoculation. Larvae were reared on diets that varied in the quantity of food which had the effect of modifying development time and adult body size. Wolbachia w Mel infection was associated with highly significant reductions in dengue serotype 2 (DENV-2) infection rates of between 80 and 97.5% following intrathoracic injection of adults emerging from three diet levels. Reductions were 100% in two diet level treatments following oral inoculation. Similarly, w MelPop infection was associated with highly significant reductions in DENV-2 infection rates of between 95 and 100% for intrathoracic injection and 97.5 and 100% for oral inoculation across diet level treatments. Larval diet level had no significant effect on DENV-2 infection rates in the presence of Wolbachia infection in mosquitoes that were intrathoracically injected with the virus. This indicates that the effectiveness of Wolbachia on vector competence disruption within Ae. aegypti is unlikely to be compromised by variable larval nutrition in field settings.